The underpinning of meaningful activities by brain correlates: a systematic review - Cruyt, Ellen; De Vriendt, Patricia; De Geyter, Nele; Van Leirsberghe, Janne; Santens, Patrick; De Baets, Stijn; De Letter, Miet; Vlerick, Peter; Calders, Patrick; De Pauw, Robby; Oostra, Kristine; Van de Velde, Dominique (Frontiers in Psychology, 2023)
Introduction: Engaging in meaningful activities contributes to health and well-being. Research identifies meaningfulness by analyzing retrospective and subjective data such as personal experiences in activities. Objectively measuring meaningful activities by registering the brain (fNIRS, EEG, PET, fMRI) remains poorly investigated. Method: A systematic review using PubMed, Web of Science, CINAHL, and Cochrane Library. Findings: 31 studies investigating the correlations between daily activities in adults, their degree of meaningfulness for the participant, and the brain areas involved, were identified. The activities could be classified according to the degree of meaningfulness, using the attributes of meaningfulness described in the literature. Eleven study activities contained all attributes, which means that these can be assumed to be meaningful for the participant. Brain areas involved in these activities were generally related to emotional and affective processing, motivation, and reward. Conclusion: Although it is demonstrated that neural correlates of meaningful activities can be measured objectively by neurophysiological registration techniques, ‘meaning’ as such has not yet been investigated explicitly. Further neurophysiological research for objective monitoring of meaningful activities is recommended.